Operating optimization for the heavy metal removal from the municipal solid waste incineration fly ashes in the three-dimensional electrokinetics. (August 2018) - Huang, Tao; Liu, Longfei; Zhou, Lulu; Yang, Ke
Abstract: The three-dimensional (3D) electrode has been widely studied and curiously pushed forward for the treatment of various wastewater. However, the reports on the electro-remediation of municipal solid waste incineration fly ashes using 3D electrochemical platform are scarce. In this research, the removal of heavy metals from the municipal solid waste incineration fly ashes was comprehensively investigated using a 3D electrokinetic system. Central composite design method was used based on the 31 trials and desirability functions in the 3D electrochemical process to evaluate the main effect and their interacted effect of parameter-variables on the remedial efficiencies. The maximum removal efficiencies of zinc (Zn), lead (Pb), copper (Cu), and cadmium (Cd) were 79.54%, 67.34%, 81.34%, and 59.11%, respectively. The 3D electrode system was demonstrated to be more effective in removing heavy metals from samples compared with the 2D electrokinetic process. The intensification of hydrolysis reaction and the enhancement of electromotive force were concluded based on the mechanism analysis as two main reasons in improving heavy-metal removals with a 3D electrode in the electrokinetic remediation. Graphical abstract: Image 1 Highlights: Three-dimensional electrokinetics was optimized based on central composite design. Kinetics models were constructed in both 2D and 3D electrochemical systems. Mechanisms enhancing heavy-metal removals in 3D system were thoroughly explored.